ROLE OF EMOTIONAL COMPETENCE ON MARITAL WELL-BEING - FASHIYA P. S AND JAYAN, C (ZENITH International Journal of Multidisciplinary Research, 2015)
The study examined the role of emotional competence on marital well-being. It was hypothesized that low, moderate and high groups of emotional competence will differ on marital well-being. The sample included 147 married people who were randomly drawn from various districts of Kerala irrespective of their age and duration of marriage. They were asked to report their responses for marital well-being Inventory and Emotional Competence Inventory. One- way ANOVA and Post Hoc Scheffe were conducted for hypothesis testing. From the results, hypothesis was found to be accepted. i.e.; there is a significant difference in the three groups of emotional competence in all dimensions of marital well-being (except commitment) as well as the overall marital well-being. So it is concluded that it is better to acquire the practical skills which can be learned (emotional competence)that enables the couples to fit in the outstanding performance in the wedlock for marital well-being.